DUKUNGAN KELUARGA PADA ODHA DI WILAYAH KERJA PUSKESMAS KALIWEDI KABUPATEN CIREBON - Dewi Erna Marisa (Jurnal Kesehatan Mahardika, 2018)
HIV AIDS is a deadly disease class in the world, especially Indonesia. This disease spreads from the nobility to street children. Case of HIV AIDS in Indonesia directed by the Directorate General of Infectious Disease (CDC) & Environmental Health (EH) Ministry of Health of the Republic of Indonesia on January 1, 2012 to December 31, 2012 as many as 21,511 cases for HIV and AIDS 5,686 cases and deaths due to HIV AIDS since April 1 1987/31 December 2012 as many as 8,235 cases (Directorate General of PP & PL, Ministry of Health, 2012). The purpose of this study was to find out how PLWHA can work in the working area of the Kaliwedi Health Center in District Of Cirebon. The type of research used is analytic research, with a cross sectional study approach. In this study a total sample of samples, namely a sample of a total of 15 families of PLWHA. In analyzing the data of people using the relationship with HIV / AIDS (P value: 0,000) in data analysis with people associated with PLWHA in the Kaliwedi Health Center working area in district of Cirebon (P value: 0,000) For the Health Center to be used with PLWHA, this can improve the quality of the family by providing counseling to the families of PLWHA